Plasma Fibrinolytic Profile in Patients with Brain Tumors - Sawaya, Raymond; Ramo, Juhani O; Glas-Greenwalt, Pia; Wu, Shu Z (Thrombosis and Haemostasis, 1991)
Changes in the fibrinolytic and coagulation values measured preoperatively in brain tumor patients have not been done systematically using individual rather than global assays. Such measurments can provide meaningful information on the status of tumor-host interactions and could potentially help in predicting thromboembolic and hemorrhagic tendencies.A complete fibrinolytic profile including total fibrinolytic activity (TFA), tissue plasminogen activator (t-PA), plasmin inhibitor (PI), plasminogen activator inhibitor (PAI), protein C (PC) and plasminogen (PLG) was obtained preoperatively in 114 brain tumor patients.PLG and PI did not show much variation among the groups. TEA was slightly reduced (15%) in patients with malignant brain tumors. t-PA, however, was abnormally low in several patients and in almost 40% of patients with brain metastasis. PAI was above the upper limit of normal in approximately 50% of the patients but particularly in glioma, glioblastoma and metastasis patients. Finally, mean PC was abnormally increased in the glioblastoma and metastasis groups (p <0.001). This is the first study that has measured protein C in brain tumor patients.In conclusion, plasma fibrinolytic levels show marked changes in a substantial number of brain tumor patients prior to surgery - suggesting an ongoing tumor-host interaction.